The Enlargement of the European Union and the Redistribution of Seigniorage Wealth - Holger Feist (Center for Economic Studies and ifo Institute (CESifo), 2001)
In the course of the EU enlargement process, the participation of accession countries in the European Monetary Union might lead to a significant redistribution of seigniorage wealth if current regulations prevail. In general, accession countries will be winners from this redistribution, for example Poland with 12.9 billion euros, Romania with 9.9 billion euros or Hungary with 3.3 billion euros. Correspondingly, the current member countries of the European Union face costs of 35.3 billion euros in total, the biggest part of which has to be borne by Germany.
Keywords: 330; European Currency Union; transition economies; European integration; central banks; seigniorage